Teoretyczne i praktyczne podstawy nauczania języka specjalistycznego ESP - Donesch-Jeżo, Ewa (Theoretical and Practical Basis of Teaching English for Specific Purposes (ESP), 2008)
In the age of rapidly developing international scientific co-operation and trade, courses of foreign language for specialist purposes are becoming more and more popular. These courses are conducted on the basis of the approach called English for Specific Purposes (ESP). This approach assumes that lan-guage teaching should be adjusted to specific linguistic and communicative needs of particular learners with special attention to sociocultural context in which they use or will use English language. In order to tailor the course to the learners' professional needs, the ESP course should be preceded by the analysis of the learners' needs related to their future professional work and plans for the future, the target situation analysis, which means identifying the features of a particular situation in which the students will use a foreign language and discourse analysis, that is, the analysis of the language used in these situations. The source of information on the students' needs are students themselves, the academic teachers and the employers. Methods of collecting the information include questionnaires, interviews and talks. All these procedures aim at maximization of the efficacy of the teaching process. Teaching English for Business Purposes (EBP) aims at preparing present and future businessmen to use a foreign language at their work. Therefore, in teaching EBP the greatest attention should be focused on acquiring communicative skills indispensable for conducting business negotiations, presentations, participation in meetings, talking to clients, writing letters and reports. Courses of this type should take into consideration cross-cultural aspect. The teaching methods include problem-solving, simulations, role-play, case-study and discourse analysis.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 193-201